Outcomes of endoscopic surgery compared with open surgery for carpal tunnel syndrome among employed patients: randomised controlled trial. Issue 7556 (15th June 2006) - Atroshi, Isam; Larsson, Gert-Uno; Ornstein, Ewald; Hofer, Manfred; Johnsson, Ragnar; Ranstam, Jonas
Abstract: Objectives To compare endoscopic and open carpal tunnel release surgery among employed patients with carpal tunnel syndrome. Design and setting Randomised controlled trial at a single orthopaedic department. Participants 128 employed patients aged 25-60 years with clinically diagnosed and electrophysiologically confirmed idiopathic carpal tunnel syndrome. Main outcome measures The primary outcome was severity of postoperative pain in the scar or proximal palm and the degree to which pain or tenderness limits activities, each rated on a 4 point scale, transformed into a combined score of 0 (none) to 100 (severe pain or tenderness causing severe activity limitation). The secondary outcomes were length of postoperative work absence, severity of symptoms of carpal tunnel syndrome and functional status scores, SF-12 quality of life score, and hand sensation and strength (blinded examiner); follow-up at three and six weeks and three and 12 months. Results 63 patients were allocated to endoscopic surgery and 65 patients to open surgery, with no withdrawals or dropouts. Pain in the scar or proximal palm was less prevalent or severe after endoscopic surgery than after open surgery but the differences were generally small. At three months, pain in the scar or palm was reported by 33 patients (52%) in the endoscopic group and 53 patients (82%) in the open group (number needed to treat 3.4, 95% confidence interval 2.3 to 7.7) and the mean score difference for severity of pain in scar or palm and limitation of activity was 13.3 (5.3 to 21.3). No differences between the groups were found in the other outcomes. The median length of work absence after surgery was 28 days in both groups. Quality of life measures improved substantially. Conclusions In carpal tunnel syndrome, endoscopic surgery was associated with less postoperative pain than open surgery, but the small size of the benefit and similarity in other outcomes make its cost effectiveness uncertain.